Achievement of Basic Immunization Seen from the Distance from Home to Health Services and the Affordability of Access to Health Services in the Work Area of Banggai Timur Raya Public Health Center, Banggai Laut Regency, Central Sulawesi Province - Risna Lam Ali; Miftakhur Rohmah; Riza Tsalatsatul Mufida (Journal of Health Science Community, 2024)
The low attendance of posyandu mothers, the long distance from home to health facilities and even transportation difficulties to reach health services. The aim of this research is to determine the relationship between the achievement of basic immunization seen from the distance from home to health services and the affordability of access to health services in the work area of Banggai Timur Raya Health Center, Banggai Laut Regency, Central Sulawesi Province. Method: The design of this research is correlational research with a cross sectional approach. Respondents were taken using a purposive sampling technique who met the inclusion and exclusion criteria with a sample of 30 people. The independent variables are Distance from Home to Health Services and Affordability of Access to Health Services and the dependent variable is Achievement of Basic Immunization. Statistical test results using Chi Square. Results: The results showed that almost all 25 respondents (83%) were in the close category. Almost all 25 respondents (83%) with affordable access to health services are in the affordable category. Nearly all 26 respondents (87%) achieved basic immunization in the achieved category. The results of data analysis show that the significance level is 0.000 < α = 0.05 so that H0 is rejected and H1 is accepted, thus there is a relationship between the distance from home to health services and the affordability of access to health services with the achievement of basic immunization in the work area of the Banggai Timur Raya Public Health Center, Banggai Laut Regency, Sulawesi Province. Middle. Based on the research results, it can be concluded that the closer the house is to health services and the affordability of access to health services, the more basic immunization will be achieved for children.